Popularization Strategies in Eliminating Knowledge Asymmetry in Expert-Lay Discourse - Olga A. Boginskaya (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2023)
The article examines replies of healthcare professionals on ask-a-doctor forums, which have barely been treated in terms of popularization strategies employed in expert-lay interactions where a set of specialized concepts needs to be displayed in a way that enables lay users to understand them. The study was thus motivated by the lack of explicit guidance for healthcare professionals who are to interact with lay persons, and challenges faced by lay users in attempting to understand abstract specialized concepts. The study is based on the assumption that popularization strategies improve comprehensibility of medical information, prevent the emergence of communicative problems, and contribute to the dissemination of medical knowledge to a lay audience. A taxonomy of the strategies used by healthcare professionals in disseminating medical knowledge on ask-a-doctor forums is built, linguistic markers that signify these strategies in expert-lay interactions are identified. A corpus-based analysis revealed that definitions, denominations and reformulations were the most common tools employed by doctors to communicate specialized knowledge to lay-forum users. Metaphors and scenarios were infrequent in the corpus. Combined strategies were also used in doctors' replies, but their share was insignificant. It was concluded that the use of popularization tools in disseminating medical knowledge is an effective discursive mechanism that facilitates understanding among lay addressees and produces specific reactions by resorting to familiar concepts and domains.